On the Aesthetics of 15th-Century Chansonniers - Alden, Jane (Danish Yearbook of Musicology, 2006)
The most distinct aspect of 15th-century chansonniers is their simultaneous presentation of text, music, and image. Whether their owners looked on these books as records of past musical events or repositories for future occasions, the songs they contain acquired a visual identity from their elegant presentation in these small, deluxe, personal manuscripts. The inclusion of decorative borders and illuminated initials expanded the appeal of chansonniers to readers with varied levels of musical literacy. As such, these books were able to symbolize and represent the musical interests of their patrons in very tangible terms. The attention paid by scribes to the visual representation of music can be seen in the well-designed page layout, clarity of musical notation, and musical iconography. Decorative characters in initials (here and elsewhere) often play horns or trumpets, but for a number of figures in these manuscripts the wind instruments they play are parts of their own bodies. This playful embodiment of music suggests that chansonniers were valued as musical objects even by those unable to read their contents.